Effect of irrigation technique for removal of triple antibiotic paste on bond strength of MTA to root dentin - Aysin DUMANI; Sehnaz YILMAZ; Oguz YOLDAS; Zeliha Gonca BEK (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract This study evaluated the bond strength of mineral trioxide aggregate (MTA) to root canal dentin after the performance of various irrigation procedures to remove triple antibiotic paste (TAP). A total of 56 single-rooted human mandibular premolars were instrumented using a rotary system to size 40 and divided randomly into a control group (no intracanal dressing) and three experimental groups (TAP application for 28 days). TAP was then removed by rinsing with 10 mL 2.5% NaOCl using three irrigation systems (Vibringe sonic irrigation, CanalBrush, and syringe irrigation). The coronal and middle parts of root canals were then obturated with MTA. After storage for 1 week, each specimen was embedded in an acrylic block and sectioned horizontally (2-mm-thick slices) at two levels (coronal and middle). Bond strength of MTA to root canal dentin was assessed in 28 samples per group via push-out test using a universal testing machine. Data from the four groups were compared using one-way analysis of variance. Tukey's test was used for multiple comparisons. Push-out bond strength values were significantly higher in the control and Vibringe groups than in the CanalBrush and syringe irrigation groups (p < 0.001). TAP removal from root canals with the Vibringe irrigation system may increase the push-out bond strength of MTA compared with the use of the CanalBrush or syringe irrigation.